2020
DOI: 10.1088/1755-1315/404/1/012059
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of sources and composition of marine debris in western and southern Aceh, Indonesia

Abstract: Marine debris has become an important pollution issue in recent years. Its existence has impacted to marine environment, harmed marine life, and also effected human health and lives. Marine debris study in western and southern Aceh is necessary to compare debris sources, amounts, and locations. The research outputs can provide input to the government to adopt more comprehensive policies and provide important information to targets protection in the coastal areas. Eight sites (two sites for each regency: at sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
1
0
3
Order By: Relevance
“…Several sites, such as the coasts of Takalar Regency and Makassar City, South Sulawesi, indicate a significant volume of plastic debris, with 62%-86% (Tahir et al, 2019). Plastic was also identified in 86.62% of western and southern Aceh (Fitria et al, 2019). Renjaan et al (2020) found this debris on the coast of Dullah Island, Kei archipelago, to be 46%, but on Banda Aceh, it was 92% (Ondara and Dhiauddin 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Several sites, such as the coasts of Takalar Regency and Makassar City, South Sulawesi, indicate a significant volume of plastic debris, with 62%-86% (Tahir et al, 2019). Plastic was also identified in 86.62% of western and southern Aceh (Fitria et al, 2019). Renjaan et al (2020) found this debris on the coast of Dullah Island, Kei archipelago, to be 46%, but on Banda Aceh, it was 92% (Ondara and Dhiauddin 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Selain itu, keberadaan sampah laut juga disebabkan karena adanya aktivitas rekreasi dan industri dekat pantai (Hardesty et al, 2016). Pantai Tongkaina dan pantai Talawaan Bajo, Sulawesi Utara (Djaguna et al, 2019), beberapa pantai barat-selatan Aceh (Fitria et al, 2019), wilayah utara Taiwan (Kuo dan Huang, 2014), Pantai Adriatic, Italia (Munari et al, 2016) dan masih banyak yang lainnya.…”
Section: Gambar 1 Peta Lokasi Penelitianunclassified
“…Hal-hal tersebut diprediksi menjadi salah satu penyebab banyaknya sampah di sepanjang Pantai Kuala Batu.MenurutCorcoran et al (2009), pusat akumulasi sampah laut terdapat pada pantai yang letaknya dekat dengan pemukiman padat penduduk. Selanjutnya, hasil penelitian yang dilakukan olehFitria et al (2019) di beberapa pantai yang terletak di pantai barat-selatan Aceh, menunjukkan bahwa jumlah sampah laut tertinggi ditemukan di pantai dengan kepadatan penduduk yang tinggi, daerah pantai rekreasi dan pantai yang dekat dengan pelabuhan perikanan. 7%) dan kain/turunannya (0.7%).…”
unclassified
“…Kajian komposisi sampah laut tercatat telah dilakukan hanya di lima kabupaten dari 18 kabupaten yang ada di Provinsi Aceh, yaitu Aceh Jaya, Aceh Barat Daya, Aceh Barat, Aceh Selatan, dan Banda Aceh. Komposisi sampah laut yang ditemukan di Aceh Jaya, Aceh Barat Daya, Aceh Barat, dan Aceh Selatan didominasi oleh sampah plastik dengan persentase antara 64% -86,6% dengan kelimpahan tertinggi terdapat di Aceh Barat Daya dan Aceh Selatan, terutama di kawasan wisata (Kusumawati et al, 2019;Fitria et al, 2020). Di Kotamadya Banda Aceh, penelitian tentang identifikasi sampah laut telah dilakukan dengan dua kategori, yaitu sampah laut yang terdampar di pantai dan sampah laut yang terapung di permukaan perairan.…”
Section: Pendahuluanunclassified